Altitude and regional gradients in chronic kidney disease prevalence in Costa Rica: Data from the Costa Rican Longevity and Healthy Aging Study - Harhay, Meera N. (Trop Med Int Health, 2015)
OBJECTIVES: Recent studies in Central America indicate that mortality attributable to chronic kidney disease (CKD) is rising rapidly. We sought to determine the prevalence and regional variation of CKD and the relationship of biologic and socioeconomic factors to CKD risk in the older-adult population of Costa Rica. METHODS: We used data from the Costa Rican Longevity and Health Aging Study (CRELES). The cohort was comprised of 2657 adults born before 1946 in Costa Rica, chosen through a sampling algorithm to represent the national population of Costa Ricans >60 years of age. Participants answered questionnaire data and completed laboratory testing. The primary outcome of this study was CKD, defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73m(2). RESULTS: The estimated prevalence of CKD for older Costa Ricans was 20% (95% CI 18.5 – 21.9%). In multivariable logistic regression, older age (adjusted odds ratio [aOR] 1.08 per year, 95%CI 1.07–1.10, p<0.001) was independently associated with CKD. For every 200 meters above sea level of residence, subjects’ odds of CKD increased 26% (aOR 1.26 95% CI 1.15–1.38, p<0.001). There was large regional variation in adjusted CKD prevalence, highest in Limon (40%, 95% CI 30%–50%) and Guanacaste (36%, 95% CI 26–46%) provinces. Regional and altitude effects remained robust after adjustment for socioeconomic status. CONCLUSIONS: We observed large regional and altitude-related variations in CKD prevalence in Costa Rica, not explained by the distribution of traditional CKD risk factors. More studies are needed to explore the potential association of geographic and environmental exposures with the risk of CKD.